ARAHAN PENGGUNAAN LAHAN BERDASARKAN KELAS KEMAMPUAN LAHAN DI DAS PANGKAJENE BAGIAN HULU DESA LANNE KECAMATAN TONDONG TALLASA KABUPATEN PANGKEP - Yuliana Hamid; Amir Tjoneng; Annas Boceng (Percetakan Umi Toaha Makassar, 2021)
Land use must meet the requirements necessary for the land to be productive and not be damaged for an indefinite period of time. Transfer of land use is one of the causes of damage to watersheds (DAS), causing complex physical, economic and social problems both upstream and downstream. Land resources in the upstream watershed (DAS) are easily degraded due to erosion. Therefore, the management of land resources in the upstream watershed has an increasingly important role, especially in efforts to use it in a sustainable manner. This research is descriptive qualitative. The data obtained were based on purposive sampling, for each land use and were analyzed based on the land capability classification criteria. The results showed that the Pangkajene watershed upstream of Lanne Village, Tondong Tallasa District, Pangkep Regency has five land uses, namely Protected Forest with ability class VII, rice fields, gardens and shrubs with ability class VI and settlements with land capability class IV. The suitable land uses in the land capability class are Protection Forest and shrubs. Incorrect land use, namely rice fields, gardens and settlements. Unsuitable land use, namely rice fields and gardens, is directed towards land rehabilitation, while settlements are directed to use conservation techniques in the form of leveling the land on a sloping location and mixed garden settlements with moderate density in the form of fruit plants interspersed with grass cover crops. The process of this activity is carried out by still following the pattern of community activities and the principles of soil and water conservation to increase benefits both economically and ecologically